Dramaturgy and Its Effects on Beggar's Religious Life: An Islamic Education Perspective - Nurul Azizah; Kholid Masyhari; Abdurrahman Raden Aji Haqiqi (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2022)
This study aims to reveal the beggar's dual role at the Sunan Kalijaga and Sunan Kudus Tombs. The beggar's dual role is the behavior differences in front of the congregation or the community and behind it. This type of research includes qualitative field research with an ethnographic approach that emphasizes paying attention to the meaning of the beggar's actions. The results of this study indicate that on the front stage, beggars use symbols that can support their role, while backstage, they are people who do not experience economic problems. This contradiction shows that they are less grateful and need special education to strengthen Islamic education for the community, especially Muslim beggars.